PERAN SISTEM INFORMASI MANAJEMEN DALAM MENDORONG EFISIENSI KEGIATAN OPERASIONAL PADA UMKM DI INDONESIA - Shofiana Novitasari; Nadiatuz Zain Roshadi; Titik Diyah Ayuningtiyas; Shofiana Novitasari (Universitas Tulungagung, 2025)
Management Information Systems play a critical role in enhancing operational efficiency, particularly for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This study aims to examine the contribution of MIS in improving the effectiveness and productivity of MSME operations through a descriptive qualitative approach based on literature review. The data used were obtained from secondary sources, including scientific journals, academic articles, and relevant official documents. The findings indicate that SIM contributes to integrating business processes, accelerating access to information, minimizing operational errors, and supporting faster and more accurate decision-making. However, challenges such as low digital literacy, limited financial resources, and insufficient technical training still hinder optimal system implementation. Therefore, collaboration among stakeholders is necessary to provide assistance and training so that MSMEs can fully benefit from SIM adoption. With proper application, MIS has the potential to become a strategic foundation for increasing business competitiveness and sustainability in the digital era.